2006
DOI: 10.1111/j.1526-100x.2006.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Limiting the Survival of Native Tree Seedlings Used in Conservation Efforts at the Edges of Forest Fragments in Upland Madagascar

Abstract: We tested four reforestation techniques in tropical forest fragments that were damaged by fire in upland Madagascar. We conducted a full-factorial experiment on the survival of transplanted seedlings of five native tree species in grassland plots adjacent to the forest fragments in the Ambohitantely Forest Reserve. The species studied were Dodonaea madagascariensis, Filicium decipiens, Olea lancea, Podocarpus madagascariensis, and Rhus taratana. A total of 480 seedlings were planted; 207 survived the 15 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 15 publications
4
37
0
2
Order By: Relevance
“…Instead of favorable condition for seed germination in deforested land at Dulhazara, germination rate of the studied species were quite low when compared to findings from Pareliussen et al (2006) and Anderson (1866), because of excessive biotic interference i.e. wildlife (deer, sambur, wild boar among others in forest soil seedbeds and domestic animals (cows, dogs, goats, etc.)…”
Section: Discussionmentioning
confidence: 67%
“…Instead of favorable condition for seed germination in deforested land at Dulhazara, germination rate of the studied species were quite low when compared to findings from Pareliussen et al (2006) and Anderson (1866), because of excessive biotic interference i.e. wildlife (deer, sambur, wild boar among others in forest soil seedbeds and domestic animals (cows, dogs, goats, etc.)…”
Section: Discussionmentioning
confidence: 67%
“…The lower survival rate reported in this experiment compared to the current study may be due to its longer experimental period (15 months compared to ten months) and differences in experimental conditions. With respect to the latter, it is notable that Pareliussen et al (2006) planted their seedlings in grassland whereas in the current study seedlings were planted within wooded grassland at the edge of the former forest where the environment might be expected to be closer to that within the forest. Pareliussen et al (2006) found best survival close to the forest compared to relatively far from the forest.…”
Section: Resultsmentioning
confidence: 77%
“…Pareliussen et al (2006) studied the survival and growth rates of seedlings of five native tree and shrub species planted in grassland at various distances from forest within the RS Ambohitantely. Fifteen months after planting, survival of these species ranged from 40 % to 51 %.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations